Features of National Idea’s Reflection in the Kazakh Literature (Eurasian Journal of Philology Science and Education, 2016)
In the article the essence of concept «national idea» is comprehended. The main aspects of studying of this problem in modern socially-humanities are revealed. The national idea is considered in a view of political, social-cultural, philosophical, religious, historical, is artistic-publicistic approaches. Its role and value in a life of a society and the separate person are defined. During research it is established, that the national idea embodies aesthetic and ethical ideals and values, reflects civilization potential of people. In the article the idea proves that, being the major making life of a society, it has received wide illumination in fiction. The national idea penetrates works of Kazakh writers, since the ancient period. Its sources are traced in heroic and historical legends, eposes. It becomes an integral part of akyns and zhyrau’s work. The national idea receives reflection in the modern Kazakh literature. Writers comprehend it in unity with a problem of memory, cultural continuity of generations.
Keywords: national idea; literature; writer; reflection; history; the past; person.